2020
DOI: 10.4236/jbise.2020.139019
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Dynamically Transplant into Cells in Vitro and in Mice and Rescue Aerobic Respiration of Mitochondrial DNA-Depleted Motor Neuron NSC-34

Abstract: It has been reported that transplantation of pheochromocytoma P12 and hepatoma cells' mitochondria improve the locomotive activity and prevent disease progress in experimental Parkinson's disease rats. To prepare for mitochondrial transplantation study in human neurodegenerative diseases, we select human fibroblasts as mitochondrial donor because that fibroblasts share many characteristics with mesenchymal stromal cells (MSCs). We isolate human primary fibroblasts and develop a mitochondrial DNA (mtDNA)-deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…We further investigated the expression level of mitochondrial tRNAs. Given that the expression level of mitochondrial tRNAs is a cumulative sum of contributions from many mitochondria within each cell, we normalize it by the estimated mitochondrial genome copy number per cell, which is about 300 particles in human skin fibroblasts (Jiang et al, 2020). Per mitochondrial genome copies, the expression of mitochondrial tRNA is comparable to the lowest among the cytosolic tRNAs (Figure S1A).…”
Section: Trna Levels Are Modulated In Response To Hcmv Infectionmentioning
confidence: 99%
“…We further investigated the expression level of mitochondrial tRNAs. Given that the expression level of mitochondrial tRNAs is a cumulative sum of contributions from many mitochondria within each cell, we normalize it by the estimated mitochondrial genome copy number per cell, which is about 300 particles in human skin fibroblasts (Jiang et al, 2020). Per mitochondrial genome copies, the expression of mitochondrial tRNA is comparable to the lowest among the cytosolic tRNAs (Figure S1A).…”
Section: Trna Levels Are Modulated In Response To Hcmv Infectionmentioning
confidence: 99%
“…were detected by PCR [14]. PCR was performed in a total 25 µl volume including 2 µl of PCR Master mix (Thermofisher Scientific, Waltham, MA, USA), 0.5 µl of 100 µM forward and reverse primers and 1 µl of heat-denatured imEVs samples.…”
Section: Detection Of Mitochondrial Genes By Polymerase Chain Reactio...mentioning
confidence: 99%
“…MOT is an innovative technology to transfer the isolated healthy mitochondria to injured or diseased cells. We published that the mitochondria isolated from cells [45]. Early our research showed that human normal mammary epithelial mitochondria transplanted into human breast cancer cell line MCF-7, T47D and MDA-MB-231, and suppressed glycolytic metabolism and glucose uptake of human breast cancer cells and reduced lactate production [46].…”
Section: Mot With Isolated Mitochondriamentioning
confidence: 99%